Interferon-Beta-1a (Rebif) a Risk Factor on Liver, Kidney and Sex Hormones with Multiple Sclerosis Patients: A Review - Alsaadi, Jamal Harbi Hussein (American Journal of Biomedicine and Pharmacy, 2025)
Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system (C.N.S). It is an autoimmune degenerative disease characterized by damage to the insulating myelin sheath covering the axons of the brain and spinal cord, often leading to a state of disability. The management of MS remains a major challenge. Interferon beta (IFN-β) is one of the most important licensed treatments for disease-modifying MS. interferon acts as an immunomodulation by reducing antigen presentation and T - cells. enhancing suppressor reducing pro - inflammatory cytokines, and Lymphocyte suppression migration in CNS. I.FN-β is a relatively effective Freedom of choice. Medication for patients with M.S. However, this treatment has multiple side effects, Including reactions at the injection site liver, dysfunction, decreased peripheral blood cell counts, and worsening depression. Its immunological characteristics and the genetic diversity of patients are associated with variability in response. Current review will discuss the various said effectes of interferon beta (IFN-β) at liver, kidney function at multiple sclerosis patients. The review focuses on the extent to which interferon (IFN-I) damages liver and kidney tissue, directly impacting the biology and function of many types of diseases. of kidney and liver cells. It also discusses the extent to which male and female sex hormone levels are affected, especially during pregnancy in women with MS are treatment by interferon repeatedly weekly for long periods. Conclusion: The review concluded that long-term and repeated interferon therapy has significant effects on patients with multiple sclerosis, especially on liver and kidney tissues, as well as on fetuses in pregnant women, especially in the last stages of pregnancy, which requires multiple studies to ensure the safety of multiple sclerosis patients, especially in women during pregnancy. Recommendations: The review recommends further research studies on changing the doses of interferon and adding some pharmaceutical compounds accompanying the use of interferon to reduce its potential effects on liver and kidney cells and sex hormone levels in M.S.patients.